Analysis Of Leadership Style In Improving The Performance Of Employees Of The National Narcotics Agency Of Karawang District - Muhamad Fazri Farhani; Budi Rismayadi; Wike Pertiwi (PT. Berkah Digital Teknologi, 2025)
Purpose of the study — This research aims to understand how leadership style can improve employee work performance at the Karawang Regency National Narcotics Agency office. Research method— The study employs a qualitative descriptive research technique. Data was collected using a triangulation strategy, incorporating multiple data sources, including observations, documentation, and structured interviews with 5 informants from various positions, including TU staff, rehabilitation staff, P2M staff, head of general subdivision, and eradication staff. Result— The findings indicate that the leaders at BNNK utilize a democratic leadership style, characterized by inclusive decision-making and open communication. This approach fosters a supportive work environment, encouraging employee participation and feedback. As a result, employee performance is reported to be fairly stable, with increased job satisfaction, motivation, and collaboration among staff. The democratic leadership style not only enhances team cohesion but also contributes to effective problem-solving and innovation within the agency. Conclusion— The application of a democratic leadership style by BNNK leaders positively influences employee performance at the National Narcotics Agency in Karawang, demonstrating that effective leadership is crucial for achieving organizational goals and maintaining high levels of employee engagement.